2020
DOI: 10.3390/nano10030451
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modification of Nanomicelles through Phosphatidylcholine: The Enhanced Drug-Loading Capacity and Anticancer Activity of Celecoxib-Casein Nanoparticles for the Intravenous Delivery of Celecoxib

Abstract: This study aims to stabilize loaded celecoxib (CX) by modifying the structure of casein nanoparticles through phosphatidylcholine. The results show that Egg yolk phosphatidylcholine PC98T (PC) significantly increased the stability of CX-PC-casein nanoparticles (NPs) (192.6 nm) from 5 min (CX-β-casein-NPs) to 2.5 h at 37 °C. In addition, the resuspended freeze-dried NPs (202.4 nm) remained stable for 2.5 h. Scanning electron microscopy indicated that PC may block the micropore structures in nanoparticles by ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…The amount of EL remaining in the NPs was determined using a previously reported procedure. 31 Briefly, a NP dispersion was centrifuged at 10 000 g to separate the free EL. Then, the clear aqueous phase (50 μL) was added to 450 μL of methanol to denature the protein.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of EL remaining in the NPs was determined using a previously reported procedure. 31 Briefly, a NP dispersion was centrifuged at 10 000 g to separate the free EL. Then, the clear aqueous phase (50 μL) was added to 450 μL of methanol to denature the protein.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, the same research team showed that Cx/β-CN micelles are metastable supramolecular assemblies that transform upon heating to thermodynamically stable drug free β-CN micelles while releasing their drug load [149]. More recently, Xv et al [150] showed that egg yolk phosphatidylcholine PC98T (PC) significantly increased the physicochemical stability of Cx/PC-β-CN NPs (192.6 nm) from 5 min (Cx/β-CN micelles) to 2.5 h at 37 • C. The images of these NPs are provided in Figure 15. β-CN micelles were further used in order to orally deliver a synergistic combination of a chemotherapeutic drug (Paclitaxel) (PTX) and a P-glycoprotein-specific transport inhibitor (Tariquidar) (TQD), which were individually encapsulated within these micelles, for overcoming multidrug resistance (MDR) in gastric cancer [152].…”
Section: Micellar Drug Delivery Systems Based On Proteinsmentioning
confidence: 99%
“…In another study, the same research team showed that Cx/β-CN micelles are metastable supramolecular assemblies that transform upon heating to thermodynamically stable drug free β-CN micelles while releasing their drug load [ 149 ]. More recently, Xv et al [ 150 ] showed that egg yolk phosphatidylcholine PC98T (PC) significantly increased the physicochemical stability of Cx/PC-β-CN NPs (192.6 nm) from 5 min (Cx/β-CN micelles) to 2.5 h at 37 °C. The images of these NPs are provided in Figure 15 .…”
Section: Micellar Drug Delivery Systems Based On Proteinsmentioning
confidence: 99%
“…Interestingly, these nanocarriers demonstrated synergistic effects in cancer therapy and reduced their gastric side effects. Some important formulation approaches with NSAIDs or NSAID derivatives alone and combined with chemotherapeutic agents are micelles, nanomicelles, liposomes, , transferrin-bearing vesicles, nanoparticles, , PEGylated nanocochleate, nanoexosomes, , cyclodextrins, and poloxamers (Table ).…”
Section: Novel Formulation Strategiesmentioning
confidence: 99%